Testing of Andaliman Extract (Zanthoxylum Acanthopodium Dc) With 4 Types of Solutions (Ethyl Acetate, Aquades, Methanol, And Hexane) on Growth of Bacteria Escherichia Coli - Muzafri, Al; Karno, Ria (Rifa'Institute, 2022)
In general, this study aims to see whether Andaliman extract is able to inhibit the growth of Escherichia coli microorganisms. the first step in this research is the extraction of Andaliman with 4 types of solvents (equates solvents, methanol, ethyl acetate, n-hexane). In the second stage, phytochemical tests were carried out on the andaliman extract to see the content of the active compounds in the andaliman extract, in the andaliman extract the active compounds were found to be alkaloids, steroids, and free-form triterpenes, saponins, tannins, flavonoids, and glycosides. The third stage of this study was the zone activity test. inhibit andaliman extract on Escherichia Coli assay on bay leaf extract using blank disc paper. The extract solution that has been diluted with a concentration of 25%, 50%, 75%, 100%, Andaliman extract with an ethyl-acetate solvent with a concentration of 100% has the greatest inhibition on the growth of Escherichia coli with dimensions of 19.15 mm, while the has the smallest inhibition of hexane solvent with a concentration of 25% at 5.80 mm.